Needle-stick stuffs with safety device for prevention of percutaneous injuries: a literature review - Oliveira, Adriana Cristina; Pinto, Selma Almeida; Garbaccio, Juliana Ladeira (Revista de Enfermagem UFPE on line, 2012)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –> ABSTRACT Objective: to identify the literature on the use of needle-stick stuffs with safety devices for prevention of accidents. Method: descriptive study, of the type of integrative review of literature, with a survey of articles from the following databases: MEDLINE / PubMed, LILACS, Science Direct, SCOPUS, and Cochrane, from the research question << Do the needle-stick stuffs with safety devices reduce percutaneous injuries among the health professionals? >> For the sample, we elected 15 articles, presented in a figure. Results: the analysis of the eligible articles in this review showed a significant reduction in percutaneous injuries, ranging from 0.8% to 93% among healthcare professionals, with the use of objects with safety devices within their workplaces. Conclusion: needle-stick stuffs with safety devices reduce percutaneous injuries in the healthcare services; however, we should highlight the importance of active participation of high management, administration, coordination, and healthcare professionals from hospital institutions. Descriptors: Protective Equipment; Penetrating Injuries; Health Professional. RESUMO Objetivo: identificar a literatura sobre a utilização dos materiais perfurocortantes com dispositivos de segurança para prevenção de acidentes. Método: estudo descritivo, tipo revisão integrativa de literatura, com levantamento de artigos das seguintes bases de dados: MEDLINE/PubMed, LILACS, Science Direct, SCOPUS e Cochrane, a partir da questão de pesquisa << Os materiais perfurocortantes com dispositivos de segurança reduzem os acidentes percutâneos entre profissionais de saúde? >> Para amostra, elegeram-se 15 artigos, apresentados em uma figura. Resultados: a análise dos artigos evidenciou significativa redução dos acidentes percutâneos, com variação entre 0,8% a 93%, entre profissionais de saúde, com a utilização de materiais com dispositivos de segurança em seus locais de trabalho. Conclusão: materiais perfurocortantes com dispositivos de segurança reduzem os acidentes percutâneos nos serviços de saúde; entretanto, destaca-se a importância da participação ativa da alta direção, administração, coordenações e profissionais de saúde das instituições hospitalares. Descritores: Equipamentos de Proteção; Ferimentos Penetrantes; Profissional de Saúde. RESUMEN Objetivo: identificar la literatura sobre la utilización de los materiales perforo cortantes con dispositivos de seguridad en la prevención de accidentes. Método: estudio descriptivo, tipo revisión integrativa de literatura con levantamiento de artículos de las bases de datos MEDLINE/Pubmed, LILACS, Science Direct, SCOPUS y Cochrane, a partir de la cuestión de investigación << Los materiales perforo cortantes con dispositivo de seguridad reducen los accidentes percutáneos entre los profesionales sanitarios >> Para muestreo, se eligieron 15 artículos, presentados en una figura. Resultados: el análisis de los artículos denotó una significativa reducción de los accidentes percutáneos con variación entre 0,8% al 93%, entre profesionales sanitarios, con el empleo de materiales con dispositivos de seguridad en sus locales de trabajo. Conclusión: materiales perforo cortantes con dispositivos de seguridad reducen los accidentes percutáneos en los servicios sanitarios, aunque se destaca la participación activa de la alta dirección, administración, coordinaciones y profesionales sanitarios de las instituciones hospitalarias. Descriptores: Equipos de Protección; Heridas Penetrantes; Profesional Sanitario.